Hapten synthesis and influence of coating Ligands on enzyme-linked immunoreaction of DDT - Hong, JY; Kim, JH; Choi, MJ (KOREAN CHEMICAL SOC, 2002)
For the development of immunodetection method of 4,4'-dichlorodipheny-2,2,2-trichloroethane (p,p'-DDT), a persistent and broad toxic organochlorine insecticide, various DDT derivatives were synthesized and characterized for the use of immunogens and the coating ligands for the antibody evaluation. The appropriate lengths of linkers were introduced to investigate more efficient DDT derivatives. Among these hapten derivatives, 2,2-Bis(4-chlorophenyl)acetic acid (DDA), 5,5-Bis(4-chlorophenyl)-5-hydroxypentanoic acid (DDHP) and 5,5-Bis(4-chlorophenyl)-5-chloropentanoic acid (DDCP) were conjugated with keyhole limpet hemocyanin (KLH) for the use of immunogen to produce antibodies. 6,6-Bis(4-chlorophenyl)-6-hydroxyhexanoic acid (DDHH) and 3-[6,6-Bis(4-chlorophenyl)-6-hydroxyhexanoylamino]propanoic acid (DDHHAP) in addition to above hapten derivatives were conjugated to ovualbumin (OVA) and bovine serum albumin (BSA) for the use of coating ligands to measure the titration level of antibody and the displacement of free analytes. Three matching pairs of antibodies and coating ligands were selected for the simultaneous detection of p,p'-DDT and its related compounds of DDA and 2,2-bis(4-chlorophenyl)-1,1-dichloroethylene (p,p'-DDE) by investingating the displacement of free analytes in an indirect ELISA. These were PAb#1 and coating ligand DDCP-OVA, PAb#1 and DDHHAP-OVA, and PAb#3 and DDHHAP-OVA. The most useful immunoreaction for DDT analytes were obtained using PAb#3 and coating ligand DDHHAP-OVA showing 3.4 ng/mL of lower limit of detection. These results indicated that titration level and free analytes displacement were greatly influenced by hapten derivatized and carrier proteins conjugated.
Keywords: MONOCLONAL-ANTIBODIES; PESTICIDES; RESIDUES; SAMPLES; AMIDES; ACIDS; DELHI; SOIL